Articles of Agreement. (International Monetary Fund, 2011)
Last issued in 1992, this new release of the IMF's Articles of Agreement for 2011 includes changes to the Articles resulting from the adoption of the Fourth Amendment on August 10, 2009, as well as the Fifth and Sixth Amendments, which entered into force on February 18, 2011 and March 3, 2011, respectively.